2005
DOI: 10.1055/s-2005-917084
|View full text |Cite
|
Sign up to set email alerts
|

Direct Acylation across a Silyloxy System of Glycerol with Carboxylic Acid Anhydrides: A Novel Strategy to the Prodrug Carrier Modules - 1,3-Diacyl-sn-glycerols

Abstract: Trichloroacetylation of 1-acyl-3-O-tert-butyldimethylsilyl-sn-glycerols, followed by a direct conversion of the silyl protecting group into an ester functionality by means of a reagent system: tetra-n-butylammonium bromide (TBABr)-trimethylsilyl bromide (TMSBr)-carboxylic acid anhydride (CAA), constitutes an efficient protocol for the preparation of enantiomerically pure 1,3-diacyl-sn-glycerols in high yields.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
11
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 14 publications
0
11
0
Order By: Relevance
“…As shown in entry 3, TFAA in the presence of TMSX (X = Cl, Br, or I), was also inefficient in replacing the trimethylsilyl group in the model substrate by a trifluoroacetyl one, although it is known that this system generates highly electrophilic species, trifluoroacetyl halides. [54] The latter reactions, however, could be rescued by the addition of the corresponding Bu 4 NX (entry 4).…”
Section: Synthesis Of C3-vicinal Haloalkanols (16-20) (Route B Schemmentioning
confidence: 97%
See 2 more Smart Citations
“…As shown in entry 3, TFAA in the presence of TMSX (X = Cl, Br, or I), was also inefficient in replacing the trimethylsilyl group in the model substrate by a trifluoroacetyl one, although it is known that this system generates highly electrophilic species, trifluoroacetyl halides. [54] The latter reactions, however, could be rescued by the addition of the corresponding Bu 4 NX (entry 4).…”
Section: Synthesis Of C3-vicinal Haloalkanols (16-20) (Route B Schemmentioning
confidence: 97%
“…[54] Although utility of this reagent can be extended to the production of vicinal bromoesters, it appeared to be less suitable for the synthesis of C2-O-acylated C3-vicinal chloro-and iodohydrins from the corresponding O-trimethylsilyl congeners (e.g., type 4 and 8, Scheme 6) as a result of the competitive formation of bromohydrin byproducts (ca. 10-20 %, 1 H and 13 C NMR spectroscopy).…”
Section: Synthesis Of C3-vicinal Haloesters (21-27) (Route C Scheme 6)mentioning
confidence: 99%
See 1 more Smart Citation
“…As shown in entry 3, TFAA in the presence of TMSX (X = Cl, Br or I) was also inefficient in replacing the trimethylsilyl group in the model substrate by trifluoroacetyl, although it is known that this system generates highly electrophilic species, trifluoroacetyl halides. 25 The latter reactions, however, could be rescued by the addition of the corresponding Bu 4 NX (entry 4).…”
mentioning
confidence: 99%
“…Since we previously found that treatment of carboxylic acid anhydrides with TMSX (e.g. X = Br or I, 1.0 equiv) at room temperature led to almost instantaneous formation of equimolar amounts of the corresponding acyl halides (ACX) and trimethylsilyl carboxylates (ACOTMS), 34 we carried out additional experiments to elucidate mechanistic contribution of these species in the haloacylating cleavage of the aforementioned oxirane systems. 1 H NMR and 13 C NMR spectroscopy revealed that acetyl bromide (1.5 equiv) alone effected opening of the oxirane ring of glycidyl oleate 1 with a predominant migration of the oleoyl moiety affording a mixture of 1-acetyl-2oleoyl-and 1-oleoyl-2-acetyl-3-bromoglycerol in a ratio of 80:20 (CH 2 Cl 2 , r.t., 72 h, isolated yield as a mixture: ca.…”
mentioning
confidence: 99%